Promethium: To Strive, to Seek, to Find and Not to Yield - Elkina, Veronika; Kurushkin, Mikhail (Frontiers in Chemistry, 2020)
Promethium (Pm), element #61, got its name from the Greek Titan Prometheus, who stole fire from Zeus and passed it to people. The only element in the lanthanide series of the periodic table with no stable isotopes, Pm has found an impressive number of applications since its announcement in 1947 after World War II. Despite promethium having 38 known isotopes, 147Pm is by far the most utilized and useful one. Promethium is used in long-life atomic batteries for satellites or space probes, satellite-to-submarine laser communication systems, “cosmic clocks” for the measurement of cosmic rays lifetime, monitoring of the changes in water content of citrus leaves caused by wetting and drying cycles in the soil, radiotherapy and even for prevention of dandruff, to name but a few applications. During the Moon expeditions, Pm was used to illuminate instruments in the Apollo landing modules; currently it is used during preparations for long-term interplanetary missions (e.g., Mars) to simulate space conditions on Earth. This mini review offers a comprehensive illustration of promethium’s history, synthesis techniques, properties and its major applications in science, technology and everyday life.